Domain model as problem-oriented architecture application for mobile applications - Zaragoza, Mechelle Grace; Kim, Haeng Kon; Hwang, Ha Jin * (2017)
Domain modeling is an activity that develops a generic model of a family of systems. It has been considered as one of the significant activities in systematic reuse. Frameworks can be used for allowing the design layers, permitting the construction of an intricate structures and reusing development information. In this paper, we will discuss the domain modeling supporting tool that extracts candidate domain model objects to construct frameworks from domain descriptions in a typical text form.